Correlation of Midwives’ Knowledge about COVID-19 to Anxiety in Providing Care during COVID-19 Pandemic - Vide Bahtera Dinastiti; Susanti Tria Jaya; Ratna Feti Wulandari (Universitas Islam Bandung, 2022)
The increasing incidence of COVID-19 cases caused anxiety for medical workers. Knowledge about COVID-19 is an element that works on medical workers' anxiety levels, including midwives. This study aimed to analyze midwives' knowledge about COVID-19 to the midwives' anxiety in providing midwifery care during the COVID-19 pandemic. This correlational analytic study was conducted between August and October 2021 in RSUD Kabupaten Kediri. A self-administered questionnaire containing knowledge and Zung Self-Anxiety Rating Scale questions was distributed to 45 respondents to complete. The correlation between midwives' knowledge about COVID-19 in midwives' anxiety was examined using Kendall's tau correlation test. The outcomes pointed out that most respondents had good knowledge of approximately COVID-19 (89%), and most of the respondents had moderate anxiety (84%). The analysis showed that there had been a correlation between knowledge about COVID-19 to the anxiety of midwives in providing care. The correlation coefficient value of −0.235 with a significance level of 0.036 indicated that the better the knowledge, the lighter the anxiety of the midwives. Therefore, it's essential to increase the understanding of midwives about COVID-19 and to review other factors that can affect the anxiety of midwives in providing care.